Neutropenia febril en pacientes con neoplasias hematológicas y microorganismos asociados a la infección (2017)
Introduction: Cancer is defined as the non-controlled proliferation of abnormal cells which can affect well-functioning of vital body organs, in there is a tissue growth by the unregulated proliferation of tumor cells that are noxious and cause invasion and or metastasis. Febrile neutropenia is considered as one of the main clinical complications within patients with radiotherapy and chemotherapy treatment as control of neoplasm. Objective: Describe the importance of febrile neutropenia and associated infections in patients with hematological neoplasm. Methodology: An electronic bibliographic revision was made, pointing 52 arcticles with an extense search in data bases like Scielo, ScienceDirect, Medigraphic, PubMed, Redalyc; published between 2011 and 2017, taking account of key words such as febrile neutropenia, cancer, bacterial infections and fungal infections. Conclusion: Febrile neutropenia is one of the major complications frequently presented by patients diagnosed with hematologic neoplasm that receive radiotherapy and chemotherapy treatment, due to the affection of neutrophils physiopathology by cytotoxic therapy; these patients are widely exposed to suffer several infections, which is why clinical surveillance and empirical therapy are both important.